Menganalisis Perbandingan Administrasi Publik di Negara Jerman dan Perancis - Dahlan, Ama Ilhamri Bin; Anjani, Cahya Eka; Andalas, Fithria Sari; Rafi, Nazwa Aisyarah; Anggraeni, Salma Dyahning (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This article compares German and French state administration, highlighting differences in state form, political systems, as well as resource, historical, moral and economic factors. Germany itself, with a strong federal and decentralized system, is different from France which is a unitary country with dominant centralization. German politics is also based on a multiparty system that encourages consensus, while France has a semi-presidential system with significant executive powers. HR in Germany emphasizes meritocracy, while France is more bureaucratic. In terms of natural resources, Germany focuses on energy efficiency and green technology due to limited resources, while France has advantages with nuclear energy, a strong agricultural sector, and mineral reserves such as uranium and iron ore. Historically, Germany developed decentralization after World War II, while France has a tradition of centralization. From a moral perspective, Germany emphasizes collectivism, while France emphasizes egalitarianism. The German economy adopts a social market model, while France has a mixed economy with higher government intervention. This analysis shows how these factors influence state administration in both countries and provides important insights for governance studies.